2016
DOI: 10.1353/hpu.2016.0160
|View full text |Cite
|
Sign up to set email alerts
|

HIV Diagnosis, Linkage to Care, and Retention among Men Who Have Sex with Men and Transgender Women in Guatemala City

Abstract: Men who have sex with men (MSM) and transgender women are disproportionately affected by HIV in Guatemala, yet little is known about their experiences with diagnosis, linkage to care, and retention. We conducted qualitative interviews with 26 MSM and transgender women living with HIV in Guatemala City. HIV diagnosis experiences changed over time with increasing asymptomatic testing at non-governmental organizations. Fear of the physical and social impacts of HIV delayed testing, acceptance of diagnosis, and li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
22
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 17 publications
1
22
0
3
Order By: Relevance
“…As trajetórias de muitas delas são marcadas por violações aos direitos humanos, com histórias de encarceramento policial por conta da identidade de gênero 18,19 , criminalização 20 e violência 21 . Nos serviços de saúde, muitas também enfrentam discriminação e possuem pouco acesso 21,22,23,24 . Além disso, enfrentam a ausência de acesso ao uso adequado de hormônios 13,20 e de procedimentos cirúrgicos para modificação corporal 25 .…”
Section: Introductionunclassified
“…As trajetórias de muitas delas são marcadas por violações aos direitos humanos, com histórias de encarceramento policial por conta da identidade de gênero 18,19 , criminalização 20 e violência 21 . Nos serviços de saúde, muitas também enfrentam discriminação e possuem pouco acesso 21,22,23,24 . Além disso, enfrentam a ausência de acesso ao uso adequado de hormônios 13,20 e de procedimentos cirúrgicos para modificação corporal 25 .…”
Section: Introductionunclassified
“…Most patients felt ashamed of their disease and feared the social and physical consequences. This led to delayed HIV testing and dissuaded participants from accessing care, closely corresponding to findings in Lima and Guatemala (28), (39). Addressing treatment adherence-related misinformation and providing access to social support in a culturally sensitive manner has been found to improve adherence by Simoni et al (54).…”
mentioning
confidence: 73%
“…A worldwide search identified 16 relevant qualitative papers in HIV-positive men who have sex with men in regard to barriers to care; the majority undertaken in Africa and Asia. Stigma relating to HIV status and sexuality was a recurring theme as a barrier to disease control (34)(35)(36)(37)(38)(39). Two studies in China identified barriers to care in men who have sex with men as negative coping and mental health, misconceptions of ART benefits, non-disclosure of HIV status and lack of trust in the health services (34), (35).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A worldwide search identified 16 relevant qualitative papers in HIV-positive MSM in regard to barriers to care; the majority undertaken in Africa and Asia. Stigma relating to HIV status and sexuality was a recurring theme as a barrier to disease control (34)(35)(36)(37)(38)(39). Two studies in China identified barriers to care in MSM as negative coping and mental health, misconceptions of ART benefits, non-disclosure of HIV status and lack of trust in the health services (34), (35).…”
Section: Introductionmentioning
confidence: 99%